Novel Cysteine Desulfidase CdsB Involved in Releasing Cysteine Repression of Toxin Synthesis in Clostridium difficile - Gu, Huawei; Yang, Yingyin; Wang, Meng; Chen, Shuyi; Wang, Haiying; Li, Shan; Ma, Yi; Wang, Jufang (Frontiers in Cellular and Infection Microbiology, 2018)
Clostridium difficile, a major cause of nosocomial diarrhea and pseudomembranous colitis, still poses serious health-care challenges. The expression of its two main virulence factors, TcdA and TcdB, is reportedly repressed by cysteine, but molecular mechanism remains unclear. The cysteine desulfidase CdsB affects the virulence and infection progresses of some bacteria. The C. difficile strain 630 genome encodes a homologue of CdsB, and in the present study, we analyzed its role in C. difficile 630Δerm by constructing an isogenic ClosTron-based cdsB mutant. When C. difficile was cultured in TY broth supplemented with cysteine, the cdsB gene was rapidly induced during the exponential growth phase. The inactivation of cdsB not only affected the resistance of C. difficile to cysteine, but also altered the expression levels of intracellular cysteine-degrading enzymes and the production of hydrogen sulfide. This suggests that C. difficile CdsB is a major inducible cysteine-degrading enzyme. The inactivation of the cdsB gene in C. difficile also removed the cysteine-dependent repression of toxin production, but failed to remove the Na2S-dependent repression, which supports that the cysteine-dependent repression of toxin production is probably attributable to the accumulation of cysteine by-products. We also mapped a δ54 (SigL)-dependent promoter upstream from the cdsB gene, and cdsB expression was not induced in response to cysteine in the cdsR::ermB or sigL::ermB strain. Using a reporter gene fusion analysis, we identified the necessary promoter sequence for cysteine-dependent cdsB expression. Taken together, these results indicate that CdsB is a key inducible cysteine desulfidase in C. difficile which is regulated by δ54 and CdsR in response to cysteine and that cysteine-dependent regulation of toxin production is closely associated with cysteine degradation.